Applying the MaritimeGCH model for Greek shipping and its relevance to the Sustainable Development Goals (SDGs) - Nisiforou, Olympia; Alamanos, Angelos; Andres Garcia, Jorge; Deranian, Christopher; Papadaki, Lydia (My University, 2025)
The maritime sector faces multiple techno-economic, environmental and development challenges, requiring careful investment decisions. Several of these challenges and factors are related to the Sustainable Development Goals (SDGs). The need for holistic solutions that can address these considerations simultaneously is becoming increasingly pressing. In this chapter we present the application of a free, open-source Investment Decision Support Tool, called MaritimeGCH, to the Greek fleet as a case study example. The model aims to optimize the fleet composition (based on the minimization of the total costs) under techno-economic, environmental, operational factors and European environmental regulations. After the model description, a presentation on its application, directly and indirectly relevant to various SDGs, including: cleaner fuel mixes (SDG7 on Energy), new ships and technologies (SDG9 on Industry), policies for more environmental-friendly shipping (SDG13 on Climate Action and SDG14 on life below water), and meeting shipping demands (SDG8 on Economic Growth).
Keywords: MaritimeGCH; Fleet Optimization; Shipping; Sustainable Development Goals